NATIONAL INCOME ANALYSIS IN THE PERSPECTIVE OF ISLAMIC ECONOMICS: A MAQASID AL-SHARIAH APPROACH - Luttadinata, Zefry; Mohamad Setia Maulana Affandi; Andriani; Yuliani; Binti Mutafarida (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
National income according to maqashid syaria is a concept based on the principles of ethics and justice in the distribution of wealth and resources. Unlike the conventional approach, which focuses on output aggregation, the Islamic economic perspective positions national income as an instrument of social justice distribution. The purpose of this study is to understand the meaning and scope of national income and to understand national income from an Islamic economic perspective. The researcher's motivation in this study is the desire to analyze the potential of national income to achieve comprehensive welfare for the ummah (community). The methodology used in this study is a descriptive qualitative approach. The conclusion of this study is that in Islamic economics, the sources of state revenue are designed not only to achieve economic goals, but also to create social justice and welfare for all members of society. The novelty of this study lies in its comparison, which formulates a new integrative standard that is a new concept of measuring welfare integration that has a more comprehensive impact.